A DFT study of the chemical and optical properties of 7-atom Ag–X [X = Li, Na] nanoalloys for potential applications in opto-electronics and catalysis. Issue 119 (19th November 2015) - Debnath, Shaikat; Said, Suhana Mohd; Rabilloud, Franck; Chatterjee, Abhijit; Roslan, Muhammad Faris; Mainal, Azizah; Mahmood, Mohamad Syafie
Abstract : In this paper, Ag atoms are substituted by X (Li, Na) atoms to form Ag m X(7− m ) clusters to explore their electronic, chemical and optical properties in the framework of density functional theory (DFT). Abstract : In this paper, Ag atoms are substituted by X (Li, Na) atoms to form Ag m X(7− m ) clusters to explore their electronic, chemical and optical properties in the framework of density functional theory (DFT). The clusters are geometrically optimized without imposing symmetry and later, vibrational analysis is carried out to test the stability of the optimized structures. The calculation of ionization potential and electron affinity asserted that the Li and Na doped bimetallic clusters (especially, Ag4 Li3 and Ag3 Li4 ) are very stable in the neutral state, but their anions are expected to be very reactive. The calculated absorption spectra of the Ag m X7− m clusters have revealed that the doping of Li and Na has made the absorption band wider with regards to undoped Ag7 clusters. Therefore, this work suggests that Li and Na doping (especially, Ag4 X3, Ag3 X4 and Ag2 X5 clusters) will result in improvement of the absorption band in the 1–5 eV range, which is the prime absorption band for opto-electronic devices such as solar cells.